Luta pela terra: sentidos e ideologias do trabalho no Movimento dos Trabalhadores Rurais Sem Terra - Batista, Mariana Souza (Universidade Federal do Rio Grande do Norte, 2025)
This research aimed to analyze the characteristics of the work ideologies present in the daily lives of landless workers in the Fidel Castro and Sabaia Communes, located in CearáMirim/RN. Guided by historical and dialectical materialism and historical-cultural psychology, the study in question sought to go beyond a description of work in the Landless Workers' Movement (MST), by identifying the discourses that guide the practices of the participants, inserted in a society permeated by conflicts and contradictions around work. In the current Brazilian scenario, the MST has become the main opponent of agribusiness because it mobilizes the class struggle, disputing food production and labor relations, through agroecology and cooperation. In this context, through participant observation and semistructured interviews, we spoke with 10 landless workers. With the meanings expressed in these moments, we learned the ideologies responsible for directing the consciousness and action of the participants in relation to the capital-labor conflict in the scenario of the struggle for land. Three ideologies were identified: a) ideology of wage labor; b) ideology of selfemployment and c) ideology of work in the MST. Although the first two ideologies are manifested in the daily lives of participants to preserve the abstract nature of work, we also observe a constant movement of criticism towards them, sustained by the comparison with the work developed in the MST. The emphasis on the affections that permeate the relationship with the land, combined with the valorization of the possibility of producing and accessing healthy food as a result of one's own work, directly contrasts with the conception of work as a simple means of obtaining income. Thus, we believe that the ideology of work in the MST promotes new meanings for both work and life, pointing out paths for the construction of an alternative that challenges the impositions of capital.
Keywords: Questão agrária; Movimentos sociais; Ideologia; Marxismo; Psicologia histórico-cultural; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA